Development of listening skills in English through listening-based instruction in Western Subanon - Estioca, Sharon Joy B. (2012)
Listening is the most basic skill children use to learn a language. However, in an academic setting, this skill is the most neglected. More emphasis is given to speaking, reading and writing in the development of language proficiency. The purpose of this study was to investigate the effect of the listening-based instruction in Western Subanon (L1) on the listening comprehension skills in English (L2) of grade one native Western Subanon students. At the same time, it looked into the relationship between the listening skills in L1 and L2. It also tried to determine if the listening skills in focus are transferable from the L1 to L2, and if so, which among them is the most easily transferrable. Lastly, it aimed to determine the impact of the listening-based instruction on the participants as observed by the participants themselves, their class adviser and their parents. The investigation involved thirty-eight (38) grade one native Western Subanon pupils of the second largest public elementary school in the district of Sibuco, Zamboanga del Norte. It is located in the remote barangay of Malayal about 290 kilometers away from the capital city of Dipolog. The participants were exposed to the listening-based language lessons conducted over a period of three (3) months during the second quarter of academic year 2011-2012. Research data were gathered through a 30-item pre-post standardized listening test in English and a researcher-made counterpart test in Western Subanon. Another instrument used was a researcher-made language proficiency level indicator in Western Subanon meant to identify the participants current language proficiency in their L1. The data were analyzed quantitatively and qualitatively. For the quantitative analysis of the data, the paired t test, Pearson r and z test were used. On the other hand, the qualitative data were validated by experts. The t test indicated that there was a high significant difference between the participants pre- and post-listening test scores in English after having gone through the listening-based instruction in both L1 and L2. Further analysis revealed that there was a positive linear relationship between the listening skills in L1 and L2. In addition, data analysis showed that the listening skills were transferable from L1 to L2 with the skill of using knowledge about the world being the easiest to transfer. Finally, the study revealed that listening-based instruction had a positive impact on the participants, the class adviser and the parents as revealed by their testimonials. Therefore, the listening skills developed in the participant-learners mother tongue helped develop their listening skills in a second language which yielded a positive impact on the community. In light of these findings and conclusions, the study proposed that listening be the first skills to be developed among beginning learners. Likewise, curriculum designers should see to it that the Mother Tongue Based Multilingual Education (MTBMLE) scope and sequence logically, directly and appropriately responds to the learning needs of the students. Similarly, teachers should design and develop their own lessons and instructional materials for developing listening skills both in the mother tongue and in the second language rather than acquire commercially-produced textbooks. Moreover, early grades teachers should be native speakers or should have native-speaker-like proficiency in the learners mother tongue. Lastly, for future researchers, the study can be replicated with another group of students speaking another L1 by modifying the time frame and widening its scope to include the other macro skills and the listening comprehension components covered in this study.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: Listening -- Study and teaching (Elementary) -- Philippines -- Sibuco (Zamboanga Del Norte).; Listening comprehension -- Study and teaching (Elementary) -- Philippines -- Sibuco (Zamboanga Del Norte).; First grade (Education) -- Philippines -- Sibuco (Zamboanga Del Norte).